The Implementation of Project-Based Learning to Improving Students' Speaking Skills Through Narrative Text - Ida Ayu Oka Purnami; Ngurah Artha Yoga Pratama; Gusti Ayu Gede Sukraningsih; I Nyoman Artana (Universitas Pendidikan Ganesha, 2025)
The challenges faced by EFL students in oral communication, this study aimed to enhance their speaking skills through the implementation of individual narrative text presentation projects. The research involved 24 university students who were selected using simple random sampling. A mixed-methods design was employed, with a primary emphasis on quantitative data to measure the impact of the intervention and qualitative data to understand the students' experiences. Quantitative data were collected using speaking ability tests (pre-test and post-test), while qualitative data were gathered through participant observation. The findings revealed that the implementation of individual narrative text presentation projects significantly improved students' speaking skills, with a mean post-test score of 86.50, an increase of 16.40 from the previous mean pre-test score of 70.10. The implications of this study underscore the importance of actively and contextually integrating language skills into EFL learning, particularly through project-based activities that focus on oral communication practice, such as presentations. The results of this research recommend the use of narrative text presentation projects as an effective learning strategy to enhance the confidence and fluency of EFL students' speaking abilities.